2020
DOI: 10.6007/ijarafms/v10-i3/8083
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Firms Characteristics on Corporate Risk Disclosure: Empirical Evidence from Amman Stock Exchange

Abstract: This paper measures the extent of corporate risk disclosure and the relationship of a set of firms characteristics (firm size, type of sector, leverage, profitability, and liquidity) on the level of risk disclosure in Jordan. The measurement of risk disclosure is based on published data of sampled Jordanian firms listed on Amman Stock Exchange using the content analysis approach. The findings indicate that large firms, industrial firms, and firms with a high level of leverage and profitability disclose more ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…This finding is supported by the results of Khlif & Hussainey (2016) and Madrigal et al (2015) that large companies tend to disclose more risk information to ensure transparency due to tighter public visibility from their stakeholders including regulators and to evaluate corporate risks, especially those related to litigation and adverse reputation. Alshirah et al (2020), Soebyakto et al (2018), and Amran et al (2009 also showed that firm size has a significant influence on risk management disclosure and this reveals large and industrial companies tend to disclose broader risk information.…”
Section: Template Of Jurnal Economiamentioning
confidence: 99%
“…This finding is supported by the results of Khlif & Hussainey (2016) and Madrigal et al (2015) that large companies tend to disclose more risk information to ensure transparency due to tighter public visibility from their stakeholders including regulators and to evaluate corporate risks, especially those related to litigation and adverse reputation. Alshirah et al (2020), Soebyakto et al (2018), and Amran et al (2009 also showed that firm size has a significant influence on risk management disclosure and this reveals large and industrial companies tend to disclose broader risk information.…”
Section: Template Of Jurnal Economiamentioning
confidence: 99%